2000
DOI: 10.1128/mcb.20.23.8879-8888.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Specificity and Targeting Subunit of a Human SWI/SNF Family-Related Chromatin-Remodeling Complex

Abstract: The SWI/SNF family of chromatin-remodeling complexes facilitates gene activation by assisting transcription machinery to gain access to targets in chromatin. This family includes BAF (also called hSWI/SNF-A) and PBAF (hSWI/SNF-B) from humans and SWI/SNF and Rsc from Saccharomyces cerevisiae. However, the relationship between the human and yeast complexes is unclear because all human subunits published to date are similar to those of both yeast SWI/SNF and Rsc. Also, the two human complexes have many identical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
257
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(271 citation statements)
references
References 50 publications
14
257
0
Order By: Relevance
“…Mapping of BAF250 identi®ed the C-terminus as the region critical for GR-mediated transcription. BAF250 bound DNA, and interacted both in vitro and in vivo with the GR (Nie et al, 2000). Taken together, these data support a model in which the GR targets the BRG1 complex to the promoter by interaction with the subunit, BAF250.…”
Section: Gr and Chromatin-remodeling Complexessupporting
confidence: 69%
See 1 more Smart Citation
“…Mapping of BAF250 identi®ed the C-terminus as the region critical for GR-mediated transcription. BAF250 bound DNA, and interacted both in vitro and in vivo with the GR (Nie et al, 2000). Taken together, these data support a model in which the GR targets the BRG1 complex to the promoter by interaction with the subunit, BAF250.…”
Section: Gr and Chromatin-remodeling Complexessupporting
confidence: 69%
“…There is evidence that the GR recruits the BRG1 complex to promoters via protein ± protein interactions with BAF250, a subunit of the complex (Nie et al, 2000). In T47D human breast cancer cells lacking BAF250, addition of this BAF enhanced GRmediated transcriptional activation of a transiently introduced promoter (Nie et al, 2000). Mapping of BAF250 identi®ed the C-terminus as the region critical for GR-mediated transcription.…”
Section: Gr and Chromatin-remodeling Complexesmentioning
confidence: 99%
“…Three other Drosophila trithorax genes have been identified as SWI/SNF homologs, which, in Drosophila, are known as BRM-associated proteins or BAPs: SNR1/BAP45 is homologous to the mammalian BAF47 and to yeast SNF5 (Dingwall et al, 1995); Osa is homologous to the mammalian BAF250 and to yeast SWI1 (Collins et al, 1999;Nie et al, 2000); and Moira/ BAP155 is homologous to the mammalian BAF155/ BAF170 and to the yeast SWI3 (Neely and Workman, 2002) (Table 1). Elucidation of the role of these genes in pattern formation established a functional link between SWI/SNF activity and development in multicellular organisms.…”
mentioning
confidence: 99%
“…Recruitment of SWI/SNF to the promoter region is likely to be facilitated by NRs as transfected cell systems have shown that the chromatin remodeling complex interacts with GR in a ligand-dependent manner (Fryer and Archer, 1998). Such an interaction could be mediated through either the SNF2 (a or b) or BAF250 subunits of SWI/SNF which have been shown to interact in a ligand-stimulated manner with the ER LBD (Ichinose et al, 1997) or with full-length GR (Nie et al, 2000), respectively. In addition, the SNF2/ BAF250-containing subtype of SWI/SNF complexes also contains the subunits BAF155 and BAF170 which have been shown to interact in vitro with the zinc ®nger DBD of the transcriptional regulators EKLF and GATA1 (Kadam et al, 2000).…”
Section: Introductionmentioning
confidence: 99%